2020
DOI: 10.1016/j.heliyon.2020.e04677
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the risk of portal vein thrombosis in patients with liver cirrhosis and hepatocellular carcinoma

Abstract: The mechanisms of the hypercoagulable state in cirrhotics with and without hepatocellular carcinoma are incompetently comprehended. Objective: We aimed to explore the plasma Annexin A5/PS + MP ratio in these patients. Higher levels of Annexin A5 and PhosphatidylSerine bearing microparticles have been observed in cases of inflammation and increased coagulation but there are no studies which explore if there is an association between them and PVT in cirrhotics with and without HCC. So, our goal is to estimate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
1
7
3
Order By: Relevance
“…In summary, these results preliminarily proved that our risk gene PRKCD could either participate in the modulation of malignant biological behaviors of cancer cells as well as regulate the activation of platelets in vitro, implicating that PRKCD might act as a key molecular bridge in the cross-talk between HCC cells and platelets and also take an essential part in the platelet-induced HCC progression. Meanwhile, to explore whether platelet stimulation can mediate HCC progression by regulating the expression levels of other risk genes, based on the previous literature reports [ 22 , 23 ], we selected another two risk genes (ANXA5 and CFL1) that might be related to platelets for subsequent in vitro functional verification. And based on previous studies of these two genes in HCC [ 24 , 25 ], we synthesized two siRNA sequences respectively to knockdown the expression level of ANXA5 and CFL1 to investigate their potential function.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, these results preliminarily proved that our risk gene PRKCD could either participate in the modulation of malignant biological behaviors of cancer cells as well as regulate the activation of platelets in vitro, implicating that PRKCD might act as a key molecular bridge in the cross-talk between HCC cells and platelets and also take an essential part in the platelet-induced HCC progression. Meanwhile, to explore whether platelet stimulation can mediate HCC progression by regulating the expression levels of other risk genes, based on the previous literature reports [ 22 , 23 ], we selected another two risk genes (ANXA5 and CFL1) that might be related to platelets for subsequent in vitro functional verification. And based on previous studies of these two genes in HCC [ 24 , 25 ], we synthesized two siRNA sequences respectively to knockdown the expression level of ANXA5 and CFL1 to investigate their potential function.…”
Section: Resultsmentioning
confidence: 99%
“…Akkiz et al reported that three factors, tumor diameter >5.0 cm, tumor multifocality, and elevated alpha-fetoprotein, could be used together to predict the presence of PVTT with an OR of 17.9 [36]. In a study of 47 cirrhotic patients with hepatocellular carcinoma, Serag et al reported that Annexin A5 and phosphatidylserine-bearing microparticles may be predictive of PVTT [37]. Herein, multivariate analysis found eight factors that were used to construct our score.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 47 cirrhotic patients with hepatocellular carcinoma, Serag et al . reported that Annexin A5 and phosphatidylserine-bearing microparticles may be predictive of PVTT [ 37 ]. Herein, multivariate analysis found eight factors that were used to construct our score.…”
Section: Discussionmentioning
confidence: 99%
“…As regards blood plasma specimens, 11 genes, namely ANXA5 , ASPM , CD34 , CDC20 , CDT1 , COL4A5 , COL6A1 , ECT2 , HJURP , MCM2 , and VEGFA , presented with statistically significant differential expression between BCa and healthy individuals. In previous findings, Annexin A5 ( ANXA5 ) plasma levels were investigated as a potential biomarker for asthma diagnosis [ 109 ], pregnant and non-pregnant subjects [ 110 ], as well as for liver cirrhosis and hepatocellular carcinoma [ 111 ]. Abnormal spindle protein homolog ( ASPM ) was detected in circulating tumor cells through single-cell genomic characterization in cancer patients [ 112 ].…”
Section: Discussionmentioning
confidence: 99%